Urgensi Penerapan Constitutent Recall - Achmad Zarkasyi Yahya; Hufron Hufron (Jurnal Mengkaji Indonesia, 2023)
Abstract: So far, the concept of a recall occurring in Indonesia is fully controlled by political parties and is seen as injuring the spirit of people's sovereignty. Yet according to the constitution, the people have sovereignty. In the end, equality is realized only in the process of selecting political officials. But the people are not given the right to recall elected political officials. Precisely political parties have this right so that the sovereignty of the people shifts to the sovereignty of political parties. As a result, political officials will be more submissive and obedient to political parties than their voters. Purpose: This research aims to open updated insights regarding the concept of constituent recall or referendum recall in an effort to strengthen people's sovereignty. Design/Methodology/Approach: In this research uses the type of normative legal research. Using a statutory approach and a conceptual approach. In other words, this research aims to solve a problem over existing legal issues, of course, supported by a statute approach related to the issue raised, as well as raising cases that have permanent legal force, and using a conceptual framework that is guided by views and doctrines. legal in law. Findings: Political parties are seen as hampering the process of channeling people's aspirations within the legislature, often carrying out recalls without asking for the approval of the people and giving the main delegation to members of the DPR and DPRD. As stated in the 1945 Constitution regarding the sovereignty of the people, therefore, in the recall process, members of the legislature must include the people. This writing aims to change the process of replacing members of the legislature with the constituent recall process to involve the people dirctly in the withdrawal or replacement of members of the legislature, especially members of the DPR and DPRD in a democratic manner by prioritizing people's sovereignty so that the process becomes transparent and democratic. Originality/Value: Several research have raised the issue of recall, but what is novel in this research is the construction of recall constitutions which involves the people in order to realize people's sovereignty.